Study to assess proper timing of laryngoscopy in post-thyroid surgery patients to detect recurrent laryngeal nerve injury - Ahmed, Tausif; Rahman, Abdur; Ahmed, Aftab; Alam, Mehtab; Chand, Shruti (Asian Journal of Medical Sciences, 2021)
Background: Thyroid surgeries are commonly done nowadays for benign and malignant conditions. Recurrent laryngeal nerve palsy (RLNP) is an important and potentially catastrophic complication of thyroid surgery. The purpose of the study was to determine the impact of rigid endoscopy (Hopkins rod-lens telescope) performed at different time intervals on the diagnosis of RLNP in post-thyroid surgery patients. Aims and Objectives: To assess Proper Timing of Laryngoscopy in Post-thyroid Surgery patients to Detect RLN Injury. Materials and Methods: Rigid endoscopy was performed postoperatively at day 0 (T0), at 2nd day post-op (T1), and day 14 (T2). For patients with RLNP, repeated examinations were performed at 2 months (T3), 6 months (T4), and 12 months (T5). Results: The study included 50 patients of thyroid swelling with different diagnoses. Overall, 35 patients appeared for postoperative laryngoscopic examination of the vocal folds at our center, providing 61 nerves at risk. RLNP rate was 8.1% at T0, 11.5% at T1, 9.8% at T2, 8.1% at T3, 4.9% at T4, and 3.3% at T5. T1 was significantly superior to all other time intervals in terms of diagnosis of RLNP but statistically not significant. Conclusion: Rigid endoscopy is essential for the detection of vocal cord paralysis after thyroidectomy. We report different time evaluation criteria of vocal cord morbidity with great and significant variability of results. Second day post-op inspection of the larynx (T1) is suggested.